Exploring the attitudes of primary school mathematics teachers in Jeddah governorate towards problem solving plan lessons: Critical Ethnographic Study - Alsulami, Abdulrahman Awad; Alsulami, Naif Mastoor (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to critically examine the attitudes of mathematics teachers at primary in Jeddah governorate stage towards the lessons of the problem-solving plan, and the extent to which these attitudes affect the interest of mathematics teachers in these lessons. This research has adopted the critical ethnographic method. This research approach has allowed us to reflect critically on the attitudes of mathematics teachers towards the lessons of the problem-solving plan, as the researcher conducted interviews with six of my fellow primary school mathematics teachers. The study found that negative attitudes from teachers and lack of conviction of these lessons, either because of the lack of knowledge or its importance, which led to a lack of interest in the lessons as well as the negative impact on teaching practices in those lessons through the failure to apply problem-solving strategies. This study produced a finding that includes the need for primary school mathematics teachers for training and educational courses related to problem-solving plan lessons and workshops on how to implement strategies for solving mathematical problem.
Keywords: attitudes of mathematics teacher; problem solving plan lessons; mathematical problem; Ethnographic research